Will-substitutes in England and Wales - Braun, A (Hart Publishing, 2016)
Will-substitutes, that is to say mechanisms that are functionally equivalent to wills, are very common in the US, where much of the wealth is transferred on death by means other than wills, and thus outside traditional probate procedures. The purpose of this chapter is to investigate whether this is the case also in England and Wales. This chapter explores some of the most common mechanisms used, the rationale behind their use, as well as the consequences that arise from their proliferation. In doing so, it considers will-substitutes from different perspectives, including those of creditors and family members and dependants. It argues that the current state of the law in England and Wales is unsatisfactory and that it is time for a debate involving non-probate transfers and their relationship with current succession laws.